2020
DOI: 10.3389/fpsyt.2020.568824
|View full text |Cite
|
Sign up to set email alerts
|

Potential Neural Mediators of Mom Power Parenting Intervention Effects on Maternal Intersubjectivity and Stress Resilience

Abstract: Stress resilience in parenting depends on the parent's capacity to understand subjective experiences in self and child, namely intersubjectivity, which is intimately related to mimicking other's affective expressions (i. e., mirroring). Stress can worsen parenting by potentiating problems that can impair intersubjectivity, e.g., problems of “over-mentalizing” (misattribution of the child's behaviors) and “under-coupling” (inadequate child-oriented mirroring). Previously we have developed Mom Power (MP) parenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 107 publications
(166 reference statements)
3
27
0
Order By: Relevance
“…In a longitudinal study (Singer and Engert, 2019), distinct constructs of attention and interoception (present-moment), socio-emotional processes (compassion and loving-kindness), and meta-cognitive processes (perspectivetaking), were evaluated and found to be differentially augmented in the 9-month training program; generally, the results supported differential neural plasticity that promoted differential training effects on social cognition, altruism, and hormonal response to psychosocial stress. Notably, we recently reported how a compassion-promoting parenting intervention in mothers promoted the attunement to their child through the changes in the brain network in support of our predictions, e.g., better maternal attunement to the child was associated with decreased parenting stress and increases in attunementdependent responses in the amygdala and reality-checking networks; the training also decreased dmPFC responses that may mediate child-specific conceptual thoughts when the mothers responded to the child; the decreases in functional connectivity between PAG and dmPFC were associated with decreases in parenting stress, suggesting that maternal stress was reduced when relatively less defensive signals from PAG were channeled to the mothers' mental images of the child, which would have "stained" the maternal perception of the child (Ho et al, 2020).…”
Section: The Neuroscience Of Compassion Meditationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a longitudinal study (Singer and Engert, 2019), distinct constructs of attention and interoception (present-moment), socio-emotional processes (compassion and loving-kindness), and meta-cognitive processes (perspectivetaking), were evaluated and found to be differentially augmented in the 9-month training program; generally, the results supported differential neural plasticity that promoted differential training effects on social cognition, altruism, and hormonal response to psychosocial stress. Notably, we recently reported how a compassion-promoting parenting intervention in mothers promoted the attunement to their child through the changes in the brain network in support of our predictions, e.g., better maternal attunement to the child was associated with decreased parenting stress and increases in attunementdependent responses in the amygdala and reality-checking networks; the training also decreased dmPFC responses that may mediate child-specific conceptual thoughts when the mothers responded to the child; the decreases in functional connectivity between PAG and dmPFC were associated with decreases in parenting stress, suggesting that maternal stress was reduced when relatively less defensive signals from PAG were channeled to the mothers' mental images of the child, which would have "stained" the maternal perception of the child (Ho et al, 2020).…”
Section: The Neuroscience Of Compassion Meditationsmentioning
confidence: 99%
“…The authors of the study suggested that compassion meditation can cultivate an enhanced motivation to look at visual images depicting suffering while attenuating amygdala responses to the aversiveness of stimuli. However, an alternative interpretation may be that the compassion training increased the synchrony between the negative valence of the pictures and the valence-dependent responses in the amygdala, as suggested by a recent study on compassion-promoting parenting intervention effects on amygdala (Ho et al, 2020).…”
Section: The Neuroscience Of Compassion Meditationsmentioning
confidence: 99%
“…This can be approximated in the maternal imitation of own vs. other infant facial expressions, which predictably activated their mirror neuron brain circuits, including insula and amygdala according to maternal reflective function ( Lenzi et al, 2009 ). With an updated child face mirror task, requiring mothers to “empathically join” vs. “observe” own (vs. other’s) child’s joyful vs. distressed expressions, parenting stress was inversely associated with amygdala responses ( Ho et al, 2020 ).…”
Section: Neurobiology Of Parent-child Attachmentsmentioning
confidence: 99%
“…7B ). Finally, MP significantly increased maternal empathy-dependent amygdala responses for own versus other child’s joyful expressions ( Ho et al, 2020 ). Another intervention, Attachment and Biobehavioral Catch-up (ABC), was associated with larger increases in event related potential responses to emotional faces relative to neutral faces, which in turn was associated with observed maternal sensitivity ( Bernard et al, 2015 ) and greater responses for ~10 year olds to own mother picture cues in social cognition regions: precuneus, cingulate, and hippocampus ( Valadez et al, 2020 ).…”
Section: Neurobiology Of Parent-child Attachmentsmentioning
confidence: 99%
“…A larger community-based RCT (N = 122) found improvements in mental health and parenting stress for high-risk mothers after participating in MOM Power, in contrast to negative parenting outcomes (i.e., increase parent-child role-reversal) for the control group (Rosenblum et al, 2017). The effects of MOM Power on MBN have been examined with two fMRI studies utilizing a Child Facing Mirroring Task and fMRI (Ho et al, 2020). The authors found that participation in MOM Power led to decreased parenting stress which may have been mediated by changes in left superior-temporal-gyrus, peraqueductal gray, and left amygdala.…”
Section: More Restructures Rewardmentioning
confidence: 99%